Elementary modern standard Arabic, Part 1, Arabic pronunciation and writing ; Arabic grammar and vocabulary, lessons 1-30 - Abboud, Peter F.; McCarus, Ernest N. 1922- (Cambridge University Press, 1983)
The Elementary Modern Standard Arabic Course (EMSA), published in 1983, is the premier introduction, for the English-speaking student, to the active written language of the Arab world. Expressly designed for the beginning student, the course is written by a team of Arabic language teachers consisting of native and non-native Arabic speakers, linguists and people whose primary interests are literature and allied areas. It implements an audio-lingual approach to language teaching while presenting the elements of Modern Standard Arabic as written and spoken in the contemporary Arab World. Volume 1 is complete in itself and presents a practical introduction to the writing system of Arabic and to its pronunciation, with reading and writing pronunciation drills. Thirty lessons provide a basic working knowledge of Arabic. Each lesson contains a text, a vocabulary, grammar and drills including oral and written comprehension passages. An Arabic-English glossary completes the volume. The course continues in Volume 2, which extends the knowledge of vocabulary, grammar and expression. Fifteen further lessons are followed by appendices which give reference information